The Artificial Intelligence in Peruvian companies and labor impacts on workers - Armas Morales, Carlos (2021)
In some Peruvian companies, exploits of technological transformation, digitization and automation inherent in the use of Artificial Intelligence are observed. In this sense, the article explores and describes, from a qualitative approach, the use of artificial intelligence in Peru and the possible impact on workers due to the creation of new jobs and the disappearance of others due to the use of these technologies. The research had a qualitative approach, I used the documentary technique, interviews, survey and the normative comparison technique. The results indicate that the use of artificial intelligence in Peru by companies is incipient, but will intensify in the coming years. On the other hand, the labor regulations of the State related to these innovations are outdated, in such a way that companies that opt ??for the dismissal of surplus workers or that do not adapt to the new positions, will have difficulties, since the labor regulations do not It is updated to the new reality that mediates the right of entrepreneurs to innovate (IA) and the right of people to work.